Freaky Friday - Rodgers, Mary, 1931-2014 (Bowen Press, an imprint of HarperCollins Publishers, 2009)
A thirteen-year-old girl gains a much more sympathetic understanding of her relationship with her mother when she has to spend a day in her mother's body.